Gambaran Dukungan Keluarga Pada Anak dengan Leukemia di Yayasan Kasih Anak Kanker Indonesia - Triwahyuni, Fransisca; Lina Dewi Anggraeni; Ainum Jhariah Hidayah (PT. Pubsains Nur Cendekia, 2024)
Positive family support is beneficial for both parties and will need each other's support, as cancer patients are generally overwhelmed with anger and depression. Therefore, to foster motivation in cancer patients in undergoing treatment requires high support from family and those closest to them. Strength from within the child cancer patient will increase if it is supported by other strengths (family support). This study aims to determine the description of family support for children with leukemia at the Indonesian Foundation for Children's Cancer Care. This type of research uses quantitative with a descriptive analytic design. The sampling technique in this study ususes total mpling with a total of 48 respondents who met the inclusion criteria. The results of the univariate analysis were obtained by respondents with children aged 5 years (31.3%), the sex was obtained by the majority of respondents who were male, 29 respondents (60.4%). The level of support for families with children with leukemia at the Indonesian Foundation for Children's Cancer Care has good family support. Based on these results, parents are expected to always provide family support to children in need.